2013
DOI: 10.1074/jbc.m113.462366
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Architecture of a Sodium Channel S6 Helix

Abstract: Background:In-frame deletion mutation (Del-L955) in Na V 1.7 sodium channel from a kindred with erythromelalgia hyperpolarizes activation. Results: Del-L955 twists the S6 helix, displacing the Phe 960 activation gate. Replacement of Phe 960 at the correct helical position depolarizes activation. Conclusion: Radial tuning of the activation gate is critical to the activation of Na V 1.7 channel. Significance: Structural modeling guided electrophysiology reveals the functional importance of radial tuning of the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Modeling of Na v 1.7 also indicates that this residue contributes to the activation gate (Lampert et al, 2008; Yang et al, 2013). The Δ1750 mutation would move this residue into the membrane, substantially altering the geometry of the activation gate of Na v 1.6.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Modeling of Na v 1.7 also indicates that this residue contributes to the activation gate (Lampert et al, 2008; Yang et al, 2013). The Δ1750 mutation would move this residue into the membrane, substantially altering the geometry of the activation gate of Na v 1.6.…”
Section: Discussionmentioning
confidence: 97%
“…Nucleotides c.5248–5250 were deleted from the tetrodotoxin (TTX)-resistant derivative of the murine Na V 1.6 cDNA clone Na V 1.6R by site directed mutagenesis as previously described (Tyrrell et al, 2001; Lampert et al, 2008; Yang et al, 2013). The neuron-derived cell line ND7/23 was co-transfected with the Na v 1.6 cDNA and an eGFP cDNA using Lipofectamine 2000 (Invitrogen, Carlsbad, CA) as previously described (Sharkey et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Structural modeling was performed as described previously (Yang et al, , 2013a. Briefly, sequence alignment was achieved using ClustalW2 and manually refined (Yarov-Yarovoy et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…1B). To visualize Ala1632Gly in the folded channel, we constructed a Nav1.7 structural model (Yang et al, , 2013a (Fig. 1C) and observed that Ala1632 is positioned at the turn between the S4-S5 linker and the S5 helix of domain IV (Fig.…”
Section: Clinical Description and Molecular Geneticsmentioning
confidence: 99%
See 1 more Smart Citation